The Optimal Control and MLE of Parameters of a Stochastic Single-Species System - Huili Xiang; Zhijun Liu (Discrete Dynamics in Nature and Society)
This paper investigates the optimal control and MLE (maximum likelihood estimation) for a single-species system subject to random perturbation. With the help of the techniques of stochastic analysis and mathematical statistics, sufficient conditions for the optimal control threshold value, the optimal control moment, and the maximum likelihood estimation of parameters are established, respectively. An example is presented to illustrate the feasibility of our theoretical results.